2019
DOI: 10.1177/1557988319834843
|View full text |Cite
|
Sign up to set email alerts
|

Are Men Making Informed Decisions According to the Prostate-Specific Antigen Test Guidelines? Analysis of the 2015 Behavioral Risk Factor Surveillance System

Abstract: The prostate-specific antigen (PSA) screening recommendation endorses the opportunity for men to make an informed decision about whether or not to screen. This entails speaking with a provider to discuss the potential advantages, disadvantages, and uncertainties about the PSA screening test. The purpose of this study was to examine (a) the reported level of being informed about the PSA test by race and (b) the association between the receipt of the PSA test and participants reporting that they were informed ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…People only discussed the disadvantages of testing or discussed neither advantages nor disadvantages of testing have lower odds of testing compared with people discussed both advantages and disadvantages. This is consistent with the research results of most articles ( Bowen et al, 2011 ; Cooper et al, 2019 ; Li et al, 2015 ; Nguyen et al, 2020). This indicated shared decision making should be increased, especially for people with high risk of PCa, to improve screening rate.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…People only discussed the disadvantages of testing or discussed neither advantages nor disadvantages of testing have lower odds of testing compared with people discussed both advantages and disadvantages. This is consistent with the research results of most articles ( Bowen et al, 2011 ; Cooper et al, 2019 ; Li et al, 2015 ; Nguyen et al, 2020). This indicated shared decision making should be increased, especially for people with high risk of PCa, to improve screening rate.…”
Section: Discussionsupporting
confidence: 92%
“…However, results were inconsistent. For general population, some researches concluded black men had higher rates and odds of screening than white men (Cooper et al, 2019;Li et al,2015), while some didn't find any significant differences (Bowen et al, 2011;Nguyen et al, 2020). For specific age groups, Sammon et al (2016) reported younger black males (45-59 years old) had higher rates of screening than non-Hispanic white men of a similar age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 2011-2012 Health Information National Trends Survey, African-American men were less likely to report being engaged in SDM (40). In contrast, data from the 2015 Behavioral Risk Factor Surveillance Survey found that African-American men were more likely to have been informed about screening compared with White men (6). However, direct cross-comparison of these national surveys is complicated due to differences in aspects of SDM measured (e.g., having discussed screening vs. being informed of the pros and cons), differences in age groups of men included in the samples, and prior screening histories (e.g., never vs. ever vs. recent).…”
Section: Discussionmentioning
confidence: 92%
“…[3][4][5]. Despite this universal recommendation, data from the 2015 Behavioral Risk Factor Survey show that only a quarter (23%) of men who had undergone PSA testing within the past year had discussed the advantages and disadvantages of screening with their providers (6). There are many barriers to fully engaging patients in SDM, including the short duration of medical appointments and the need to prioritize a range of health concerns (7).…”
Section: Introductionmentioning
confidence: 99%